Obesity, physical activity and prediabetes in adult children of people with diabetes - Lidia G. Compeán-Ortiz; Laura Elena Trujillo-Olivera; Ana María Valles-Medina; Eunice Reséndiz-González; Beatriz García-Solano; Beatriz Del Angel Pérez (Universidade de São Paulo, 2018)
ABSTRACT Objectives: Determine prevalence of obesity / overweight, physical activity (PA) and prediabetes in adult children of parents with type 2 diabetes; identify differences according to sociodemographic variables, and describe the relationship of obesity/overweight with fasting glucose (FG) and glycosylated hemoglobin (A1C). Methods: Cross-sectional study in 30 Mexican families with 53 participating adult children. Obesity / overweight was determined with Body Mass Index (BMI), Waist Circumference (WC) and body fat percentage (BFP); PA with the short International Physical Activity Questionnaire (IPAQ), and prediabetes with FG. Results: 64% of participants presented obesity / overweight, 32% low PA, and 19% prediabetes. Men had higher WC than women (U= 219, p= 0.03). Women showed more BFP than men (U= 142, p <0.01). Blood glucose was related to BFP (rs= 0.336, p < 0.05), the A1C with the BMI (rs= 0.417, p <0.01), WC (rs= 0.394, p<0.01), BFP (rs= 0.494, p<0.01) and intense PA (rs= - 0.285, p<0.05). Conclusions: High prevalence of obesity / overweight and low PA were found. The FG was related only to BFP and A1C, in addition to BMI, WC and inversely with intense BP. It is recommended to modify the educational strategies of nursing at a family level.